Variety of Changes in Spatial Patterns of Residential Space in Soropadan Village as an Impact of the Development of Economic Activities - Suparno; Endah Tisnawati; Aisha Astriecia (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2022)
Reduced open land, traffic jams on the village's main road, disruption of the safety and comfort of the living environment are only a few effects that can result from the conversion of homes into student dormitories in the form of boarding houses. This also takes place in open residential neighborhoods outside of Yogyakarta, specifically in Soropadan Village, Condongcatur Village, Depok District, and Sleman. Descriptive qualitative research methodology is employed in this study. The decision is taken taking into account the occurrences that are seen in the field. Direct field observations were used to gather the primary data selection technique, which was subsequently used to collect data utilizing qualitative data techniques. In order to understand the numerous changes in the spatial pattern of residential housings discovered in the boarding house type student dormitory in Soropadan Village as a result of the development of economic activities, this study attempts to determine the tendency of the spatial pattern of settlements. The study's findings include the similarity of changes to the spatial layout of residences into boarding-type student dormitories with a linear layout, the spatial arrangement of boarding rooms and shared rooms forming a centralized layout with the shared room serving as the center of activity in student boarding houses, and the propensity to add boarding rooms. The location of the service area, including restrooms, laundry facilities, and kitchens, is always at the rear of the building, immediately before the road. Economic development, environmental changes, population increase, and the creation of local infrastructure are all reasons that can cause a home's usage to change from a residential to a dorm-style boarding house for students.